ANALYSIS OF TOURIST PERCEPTIONS OF FACILITIES AND ACCESSIBILITY OF BOSOWA BEACH - Andi Agis Alifa Batari; Ilham Junaid (Politeknik Pariwisata Makassar, 2025)
This study aims to identify the current conditions of activities and accessibility to support tourism at Bosowa Beach and analyze visitor perceptions of accessibility and facilities at Bosowa Beach. It is hoped that this research will contribute to sustainable tourism at Bosowa Beach.To ensure tourists feel comfortable and at ease during their visit, good facilities and accessibility are crucial. Good facilities are crucial for keeping visitors satisfied and wanting to return. Bosowa Beach boasts beautiful natural scenery and numerous engaging recreational activities, but research has found that supporting facilities such as public restrooms, seating, and parking areas are still lacking. Furthermore, poor roads and a lack of public transportation limit access to the beach. Bosowa Beach still faces challenges such as inadequate supporting facilities and limited road access.The research approach uses a qualitative descriptive method with the aim of describing tourists' perceptions comprehensively. Data collection techniques in this study used observation, interviews, questionnaires, and documentation studies. Observations were conducted directly in the beach area to identify the condition of facilities and accessibility. The questionnaire was structured using a Likert scale with five assessment categories, ranging from very good to very bad. The results of this study indicate that tourist perceptions of facilities and accessibility still need to be improved to support the sustainable development of Bosowa Beach tourism. This research provides strategic recommendations for managers and local governments on how to improve facilities and increase accessibility to enhance tourist satisfaction, destination attractiveness, and local economic contribution. Strategic recommendations are aimed at destination managers and local governments to improve road infrastructure, public facilities, and accessibility of tourist information. These improvements are expected to increase Bosowa Beach's popularity as a disability-friendly destination, increase tourist arrivals, and boost the local economy. This research provides important insights that will serve as a basis for developing policies related to sustainable tourism at Bosowa Beach.